Penerapan Model Pembelajaran Project Based Learning Berbantuan Media Scrapbook Terhadap Hasil Belajar Peserta Didik - Fauziyah, Diah Nur; Solihat, Ai Nur; Gumilar, Gugum (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
The research was motivated by the problem of low student learning outcomes at SMAN 1 Ciawigebang. The purpose of this study was to determine the effect of applying the project-based learning model assisted by scrapbook media in improving student learning outcomes in economic subjects. This research uses Quasi Experiment with quantitative approach. The study population was all students of class XI-C SMAN 1 Ciawigebang in the 2024/2025 school year totaling 180 students. The sample used was class XI-C1 which amounted to 36 people as an experimental class and class XI-C2 which amounted to 36 people as a control class with sampling using purposive sampling technique. Data collection techniques were carried out with multiple choice tests. Based on the results of the study, it shows that there is an influence on the project-based learning model assisted by scrapbook media in improving student learning outcomes in economic subjects, where the hypothesis test obtained a Sig value of 0.000 <0.05, which means that Ha is accepted. The average score in the experimental class is higher than the control class, so it can be concluded in this study that the project-based learning model assisted by scrapbook media can improve student learning outcomes.